An assessment of spatial comfort of ancient Indrapuri Mosque in Aceh Besar, Indonesia / Laina Hilma Sari, Izziah, Erna Meutia, Zulfian - Sari, Laina Hilma; Hasan, Izziah; Meutia, Erna; Zulfian, Zulfian (2018)
This paper aims at assessing the spatial comfort of the ancient Indrapuri mosque including thermal, daylight and acoustic performance. This ancient mosque is located in Aceh Besar and built in the 12th century. The facade has been maintained and conserved. However, some conservation steps were shifted from the principle ones such as using traditional techniques and materials. The data werecollected through survey and mechanical measurement. The results showed that some replacements are needed due tosome spatial discomforts such as higher indoor thermal performance. It is indicated in Olgyay's bioclimatic chart which also shows that the air movement should be increased to reach the comfort zone. The mosque acoustic performance has slightly high background noise,while,the sound pressure level and reverberation time still meet the standard. The daylight remains good shown by none of electrical light switched on during the day including daytime prayer i.e. Zuhr (1 pm) and 'Ashr (4 pm).